Technology-Based Socio-Economic Transformation: The Role of Community Service in Enhancing Marketing Human Resources Quality in Micro, Small, and Medium Enterprises (MSMEs) - Sutrisno, Sutrisno; Junaidi, Ahmad; Suherlan (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to examine the role of community service in driving technology-based socio-economic transformation through the enhancement of marketing human resources (HR) quality within the Micro, Small, and Medium Enterprises (MSMEs) sector. Using a qualitative approach through a literature review method, this research analyzes 22 selected scientific articles out of a total of 30 references obtained from Google Scholar and credible academic websites throughout 1989–2025. Descriptive analysis is employed to identify intervention patterns, underlying theories, and tangible outcomes of community service programs focused on strengthening digital and marketing competencies of MSME actors. The findings indicate that the integration of digital technology and participatory community mentoring can improve marketing strategy effectiveness, expand consumer reach, and reinforce the position of MSMEs in the digital economic value chain. These results are supported by the Technology Acceptance Model, Social Cognitive Theory, and Resource-Based View, which position knowledge and capability as key assets in addressing the challenges of digital transformation. This study concludes that community service oriented towards strengthening technology-based marketing serves as a strategic instrument in building MSME sustainability and improving the economic welfare of local communities.